2023
DOI: 10.3390/pathogens12020176
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge of Th22 Cell and IL-22 Functions in Infectious Diseases

Abstract: T helper 22 (Th22) cells, a newly defined CD4+ T-cell lineage, are characterized by their distinct cytokine profile, which primarily consists of IL-13, IL-22 and TNF-α. Th22 cells express a wide spectrum of chemokine receptors, such as CCR4, CCR6 and CCR10. The main effector molecule secreted by Th22 cells is IL-22, a member of the IL-10 family, which acts by binding to IL-22R and triggering a complex downstream signaling system. Th22 cells and IL-22 have been found to play variable roles in human immunity. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 184 publications
1
10
0
Order By: Relevance
“…However, some related studies reported the upregulation of IL-22-producing CD4 + T cells in patients with acute hepatitis B compared to the controls [31,33]. Also, examining the serum level of patients with mild/moderate COVID-19 and healthy controls, researcherobserved the upregulation of IL-22 cytokines levels in COVID-19 patients [34].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, some related studies reported the upregulation of IL-22-producing CD4 + T cells in patients with acute hepatitis B compared to the controls [31,33]. Also, examining the serum level of patients with mild/moderate COVID-19 and healthy controls, researcherobserved the upregulation of IL-22 cytokines levels in COVID-19 patients [34].…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported an association between increased levels of IL-22 and the severity of hepatic diseases, which can be attributed to the proliferative and anti-apoptotic effects of IL-22 [29,30]. Detrimental prion flammatory effects have been illustrated to deteriorate certain conditions, such as hepatitis B and Helicobacter pylori infection [31]; also, previous research has highlighted that IL-22 and IL-22BP have a role in liver diseases with a particular focus on the leading causes of advanced liver failure, namely liver infections, liver damage, and liver malignancies [32].…”
Section: Discussionmentioning
confidence: 99%
“…Th22 cells, as a newly defined CD4 + T cell lineage, mainly secrete cytokines such as IL-22, which play an important role in skin homeostasis and pathological state [ 56 ]. Our results showed that the number of hair follicles in the skin of Th22 differentiation-promoting factor intervention group increased significantly, and the shape of hair follicles was closer to the mature state.…”
Section: Discussionmentioning
confidence: 99%
“…Further work is needed to establish whether streptococcal skin infections induce intestinal damage or inflammation like colitis and whether increased IL-22 in the brain following CLN treatment is an unintended consequence of CLN therapy, causing gut dysbiosis and alterations through the bidirectional gut–brain axis. In addition to ILC3 cells, the Th22 subset of CD4 + cells is a primary source of IL-22 during infections [ 63 , 64 ]. Liang et al reported that TGF-β initiates the cascade of pro-inflammatory cytokines IL-17A, IL-22, and IL-6, and together, IL-17A and IL-22 are associated with skin innate immune responses [ 65 ].…”
Section: Discussionmentioning
confidence: 99%